Orthopaedics and the Physician Payments Sunshine Act: An Examination of Payments to U.S. Orthopaedic Surgeons in the Open Payments Database. (2nd March 2016) - Iyer, Sravisht; Derman, Peter; Sandhu, Harvinder S.
Abstract : Background: The U.S. Centers for Medicare & Medicaid Services (CMS) recently released the Open Payments database (OPD) detailing payments from industry to physicians and teaching hospitals. We seek here to provide an overview of the data with a focus on the orthopaedic community. Methods: We analyzed payments in the OPD from August 1 to December 31, 2013. The OPD consists of three individual databases: General Payments, Research Payments, and Ownership. Physician identification number, physician specialty, payment type, and payment value were collected. Physicians assigned to multiple specialties were excluded. Comparisons were made between orthopaedic surgeons and the remainder of the top fifteen specialties by payment value. Results: In all, 2, 697, 015 payments with physicians were recorded; 491, 223 of these payments (18.2%) were made to physicians with multiple listed specialties and were excluded. Excluding these potentially misattributed payments did not have a significant impact on the trends identified, and $394.5 million in payments remained. Orthopaedic surgeons represented 3.4% of payments but 25.6% of value, and 13, 347 orthopaedic surgeons (68.9% of all active orthopaedic surgeons) were listed in the OPD. Payments over $10, 000 represented only 1.6% of payments to orthopaedic surgeons but 75.5% of value. The majority of these payments (56.1%) were royalties. The median payment value for orthopaedic surgeons listed in the OPD was $38.11, with two payments per surgeon; the median aggregated value was $132.56 per surgeon. Orthopaedic surgeons listed in the OPD were more likely to receive payments for travel compared with all other specialties (p < 0.001) and more likely to receive payments for royalties compared with all other specialties (p < 0.001) except neurological surgery. Conclusions: Financial interactions between orthopaedic surgeons and industry are highly prevalent. A small subset of orthopaedic surgeons received large royalties, which accounted for a majority of the transactional value provided by industry. Orthopaedic surgeons were the recipients of more payments for travel and for royalties than all other specialties except neurological surgery; however, the median value of these and other payments was similar to that for other specialties.